Mechanisms of Interaction between Government and Business Structures in the Implementation of Regional Development Strategies - Yerzhanova, S.K.; Yessenali, A.Ye.; Batyrova, N.T.; Izatullayeva, B.S.; Balkanli, A.O. (BUKETOV BUSINESS REVIEW, 2023)
Object: The objective of this article is to analyze how authorities and business entities interact at the regional level. The focus is on understanding the various forms and mechanisms of this interaction. Furthermore, the goal is to create guidelines and actionable suggestions for enhancing this interaction within the context of modernizing local economies. Methods: The evaluation of the institutional environment for conducting business in different regions involves enhancing the methodology used to assess the collaboration between governmental bodies and business entities. Findings: The study also identifies and organizes the relationship between contemporary government and business interactions in terms of their forms and mechanisms. This involves a categorization process that takes into account factors including the efficiency and immediacy of their cooperation, their societal implications, the encompassed organizational frameworks, and the approaches employed to implement collaborative initiatives within the region. The research suggests that conflicts of interest arise between regional authorities and business entities within modernized regional economies. While government bodies endeavor to assign societal responsibilities to businesses and increase budget revenues, proactive business entities, on the other hand, advocate for limitations on their involvement with governmental services. Moreover, ensuring effective partnership requires pivotal measures such as substantial reduction of tax burdens and the removal of administrative hurdles that contravene the fundamental principles of mutual cooperation between the government and businesses. Conclusions: The scientific investigation has uncovered various factors that drive the emergence of social responsibility trends within business, often arising as an unintended form of behavior. Moreover, distinct criteria have been established to assess the execution of socially responsible initiatives undertaken by business entities. These criteria are categorized into two groups: one pertains to the evaluation of social responsibility actions through non-financial reporting, and the other encompasses criteria for assessing the effectiveness of the reporting itself.